Efektivitas Aplikasi BTI (Bogor Traffic Info) Dalam Mendukung Unit Pelayanan Sim Di Wilayah Hukum Polresta Bogor Kota - Harmada, Satria Ramadhani Kusuma (Police Studies Review, 2020)
Bogor City is an area with a high population density that has the potential for high motor vehicle ownership rates, this indirectly affects traffic conditions in the area. With this kind of situation and condition, it is necessary to have innovations that can support the performance of the City Bogor Police in the field of traffic management. Bogor Traffic Info (BTI) is a form of innovation in the form of an application initiated by the Bogor City Police in order to support the improvement of services to the community in the field of traffic management. However, to assess the success of implementing an innovation product, it is necessary to evaluate the effectiveness of the innovation product. The effectiveness of the application of the BTI application in the jurisdiction of the Bogor City Police is further studied using a qualitative approach with data collection techniques in the form of document study, observation and interviews of four research variables, namely an overview of the research object (Bogor City, Bogor City Police and BTI applications), public response and the applicant for a SIM extension on the BTI application, the effect of the application of the BTI application on the phenomenon of violation of the SIM rules in driving and the last factor is the aspects that affect the BTI application user to extend the SIM. Based on the results of the analysis of these four factors, it can be concluded that the application of the Bogor Traffic Info (BTI) application has not been effective in supporting the improvement of services to the community in the field of traffic management in the areas which are the responsibility of the Bogor City Police.